Analisa Faktor-faktor yang Mempengaruhi Profitabilitas Perusahaan Manufacturing yang Terdaftar di Bursa Efek Surabaya - Wiwik Retnaningsih (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This research purpose is knowing ROA industry variable influence, debt leverage, market share, capital intensive and business risk toward companies profitability and also knowing variables that are significant affect the companies probability. The research is performed in 93 manufacturing companies that are listed in Surabaya stock exchange. By researching method over 3 years began on 1993 until 1995. The statistic method that are used in analyzing data measuring the factors that affect the company's profitability is multiple regression with dependent variable (Y) is ROA of company and independent variable (X1) Is ROA of industry; while (X2) for debt leverage, (X3) for company's market share, (X4) capital intensive and (X5), variable that is the ROA of industry and business risk. From the result of R, adjusted= 0,8652 it can be said that 96,52% of the change of Y variable is caused by the changes of X1, X2, X3, X4, and X5 variable that are not included that similarly X1, X2, X3, X4, and X5 variables have influenced Y variable.